Valorization of postharvest discard of sweet cherry for the development of dehydrated fruit ingredients: compositional, physical and mechanical properties - Franceschinis, Lorena Edith (2018)
BACKGROUND: Sweet cherries are an excellent source of phenolic compounds, which may contribute to a healthy diet. The objective of this work was to generate dehydrated ingredients from postharvest discard of sweet cherries.RESULTS: Four dried ingredients were obtained from discard of fresh sweet cherry (Lapins var.), through the application of an osmotic dehydration pretreatment and freeze- or air-drying. The ingredients showed an important phenolic contribution (2.8-6.6 g gallic acid kg-1 of product) and preserved to a great extent the natural color of the fruit. Freeze-dried ingredients resulted less hygroscopic than air-dried ones, and presented a softer texture. All the ingredients were in the supercooled state at room temperature (Tg range: -23.0 to -18.8°C). Sugar infusion pretreatment caused a decrease in water sorption capacity and molecular mobility; it also reduced the initial rehydration rate.CONCLUSION: Relevant differences in nutritional and structural characteristics of ingredients were observed according to the applied processing method. These ingredients could be incorporated into different processed food as snacks, cereal mixtures, cereal bars, bakery and confectionery products. Air-dried control ingredients presented better nutritional contribution and air-dried sweet cherries with sugar infusion pretreatment could be appropriate ingredients for applications where sweet flavor and slow rehydration rate are required.